Long-Term Effects of Study Abroad: Building Global Citizenship Skills For a Contributive Way of Living - Narita, Hiromi (GILE Journal of Skills Development, 2023)
Amidst U.S. higher education institutions (HEIs), there exists a prevailing notion that global citizenship education (GCE) serves as a driving force in furnishing students with aptitudes suited for the 21st century. As a result, study abroad programs have been used as a common method to promote GCE and provide intercultural experiences for students. However, not much research has been conducted to measure the long-term effects of GCE and such study-abroad programs and how these experiences can impact participants’ characters. Employing a qualitative approach, this research delved into phenomenological interviews to reveal how study abroad has worked as GCE to foster global citizens. The subjects of this study experienced semester-abroad programs during their undergraduate program1 at a U.S. university. The research outcomes showed a multitude of insights: (1) research participants developed comprehensive perspectives regarding the concepts of global citizenship and contributing to society, irrespective of their diverse backgrounds; (2) the enduring influence of GCE and study abroad became evident in the decision-making processes related to their career and academic trajectories post-graduation; and (3) study abroad experiences substantially nurtured interviewees’ ability to navigate diverse cultures, to take purposeful action based on their established connections with others, and to perceive differences and interconnectedness. Furthermore, the research outcome showed that enduring skills and traits as global citizens could be acquired throughout the undergraduate program on a daily basis, and these skills include intercultural competence, dialogue, and understanding of interconnectedness. These results not only fill out the existing research gap but also reinforce the effectiveness of young people’s character-building as global citizens through GCE and study abroad programs.